Retention of mechanical performance of polymer matrix composites above the glass transition temperature by vascular cooling. (November 2015) - Coppola, Anthony M.; Griffin, Anthony S.; Sottos, Nancy R.; White, Scott R.
Abstract: An actively cooled vascular polymer matrix composite containing 3.0% channel volume fraction retains greater than 90% flexural stiffness when exposed continuously to 325 °C environmental temperature. Non-cooled controls suffered complete structural failure through thermal degradation under the same conditions. Glass–epoxy composites ( Tg  = 152 °C) manufactured by vacuum assisted resin transfer molding contain microchannel networks of two different architectures optimized for thermal and mechanical performance. Microchannels are fabricated by vaporization of poly(lactide) fibers treated with tin(II) oxalate catalyst that are incorporated into the fiber preform prior to resin infiltration. Flexural modulus, material temperature, and heat removal rates are measured during four-point bending testing as a function of environmental temperature and coolant flow rate. Simulations validate experimental measurements and provide insight into the thermal behavior. Vascular specimens with only 1.5% channel volume fraction centered at the neutral bending axis also retained over 80% flexural stiffness at 325 °C environmental temperature.